Determining the Risk Factors and Clinical Features Associated With Severe Gastrointestinal Dysmotility in Systemic Sclerosis. Issue 9 (6th August 2018) - McMahan, Zsuzsanna H.; Paik, Julie J.; Wigley, Fredrick M.; Hummers, Laura K.
Abstract : Objective: A subset of patients with systemic sclerosis (SSc) develop severe gastrointestinal (GI) dysmotility. We sought to determine predictors of severe SSc GI dysmotility and to identify distinct features associated with this phenotype. Methods: Patients with SSc who required supplemental nutrition (enteral or parenteral tube feeding) were compared to SSc patients with mild GI symptoms in a cross‐sectional analysis. The association between severe GI dysmotility and clinical and serologic features was examined using logistic regression. Baseline data were examined to determine predictors of developing severe GI dysfunction using Cox regression. Results: SSc patients with severe GI dysmotility (n = 66) were more likely than those patients with mild GI symptoms (n = 1, 736) to be male (odds ratio [OR] 2.47 [95% confidence interval (95% CI) 1.34–4.56]; P = 0.004), and to have myopathy (OR 5.53 [95% CI 2.82–10.82]; P < 0.001), and sicca symptoms (OR 2.40 [95% CI 1.30–4.42]; P = 0.005), even after adjustment for potential confounders. Baseline features that were associated with the future development of severe GI dysfunction included male sex (hazard ratio [HR] 2.99 [95% CI 1.53–5.84]; P = 0.001) and myopathy (HR 5.08 [95% CI 2.21–11.67]; P < 0.001). Conclusion: Distinct clinical features are present in SSc patients who are at risk of developing severe GI dysmotility. This finding is not only important clinically but also suggests that a unique pathologic process is at work in these patients.